USE OF COMBINED ORAL CONTRACEPTIVES AND THE RISK OF CERVICAL CANCER IN YOUNG WOMEN - Filho , Danillo Gondim da Silva; Martins , Gabriela de Souza; Santos , Luan Bernardino Montes; Campos , Isabela Sousa; Junior , Valdivino Soares de Oliveira; Soares , Erika dos Santos; Leit , Soraya de Souza Marques; Soares, Natascha de Prado; Cruz , Thays Souza; Bitanti , Rafael Martins; Souza , Cristiana Daniela de; Ribeiro , Bruna Martins; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
The relationship between the use of combined oral contraceptives and the risk of cervical cancer in young women has been the subject of intense scrutiny in the scientific literature. This topic, which is extremely important for women's health, has sparked debates and investigations due to the prevalence of the use of these contraceptives and the significant incidence of cervical cancer in young women. Understanding this possible association is crucial to inform contraceptive practices and cervical cancer prevention strategies. Objective: To evaluate and consolidate the available evidence on the relationship between the use of combined oral contraceptives and the risk of cervical cancer in young women, using studies and articles published in the last 10 years. Methodology: strictly adhered to the PRISMA checklist, using the PubMed, Scielo and Web of Science databases to identify relevant studies. The selected descriptors were combined oral contraceptives, cervical cancer, young women, risk and association. The search covered articles published in the last 10 years. The inclusion criteria included studies that focused exclusively on young women, directly investigated the relationship between the use of combined oral contraceptives and cervical cancer, and were published in the last 10 years. On the other hand, studies with participants outside the specific age range, research that did not directly address the association in question and articles that were not fully available or did not qualify as systematic reviews or primary studies were excluded. This methodological approach provided a comprehensive and careful analysis of the existing evidence on the topic. Results: 18 articles were selected. Analysis of studies revealed a diversity of perspectives on the association between combined oral contraceptives and cervical cancer risk in young women. Key topics included possible biological mechanisms, variations in the types of contraceptives used, and the influence of confounding factors. Conclusion: Given the complexity of the data analyzed, this review highlights the need for careful approaches in interpreting the relationship between combined oral contraceptives and cervical cancer in young women. Future research is crucial to fully clarify this association and provide more precise guidance for clinical practice.